Surian (wood as an Alternative Material for Bonded Wood Products in the Future (II): Laminated Veneer Lumber (LVL)) - Alamsyah, Eka M; Karliati, Tati (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
The objective of this study was to evaluate the performance of laminated veneer lumber (LVL) made from surian (Toona sinensis Roem) compared to sengon (Paraserianthes. falcataria L Nielsen) and rubber (karet) (Hevea brasiliensis Muell) wood which bonded with the common phenol formaldehyde (PF) and urea formaldehyde (UF) adhesives. LVL was assembled from 7 plies veneer with the final moisture content (MC) of veneer is about eight percent. The parameters of LVL i.e., MC, density, percentage of delamination, modulus of rupture (MOR), modulus of elasticity (MOE), horizontal shear strength (flat and edge direction) and formaldehyde emission were evaluated according to Japan Agricultural Standard (JAS). The result showed that delamination ratio value was zero percent. The most interesting finding was the value of formaldehyde emission of both PF and UF-surian LVL were lower than PF and UF rubber or sengon LVL due to their F4S classification of JAS. Values of MOR and horizontal shear strength both PF and UF-surian LVL was lower than rubber LVL, however it was higher than sengon LVL. The physical and mechanical properties of surian LVL met the JAS requirement.Key words: formaldehyde emission, laminated veneer lumber, physical and mechanical properties, Toona sinensis.